Problem behaviours and caregiver burden among children with Autism Spectrum Disorder in Kuching, Sarawak - Chua, Shi Yi; Abd Rahman, Fairuz Nazri; Ratnasingam, Selvasingam (Frontiers in Psychiatry, 2023)
Objective Caregivers of children with Autism Spectrum Disorder (ASD) often experience emotional and psychological distress, as well as disruptions to family life and employment due to the challenges of caring for children with ASD. This study examines the relationship between problem behaviours and caregiver burden among children with ASD. Method A cross-sectional study using convenience sampling recruited 230 caregivers of children with ASD aged 4 to 18 years from selected autism centres in Kuching, Sarawak. The caregivers completed the Aberrant Behaviour Checklist-2 and the Zarit Burden Interview. Results Univariate analysis revealed a significant difference in caregiver burden for children with ASD receiving medications (p = 0.013), registered with the Social Welfare Department (p = 0.036), and having siblings with ASD (p = 0.046). About 40% of the children exhibited at least one domain of problem behaviour. More than half of the caregivers (53.9%) experienced burden, with the majority experiencing mild burden. Positive associations were seen between irritability (r = 0.458, p < 0.01), social withdrawal (r = 0.439, p < 0.01), stereotypic behaviour (r = 0.392, p < 0.01), hyperactivity/non-compliance (r = 0.467, p < 0.01), and caregiver burden. Child factors, including the duration of problem behaviour (r = 0.182, p = 0.007), medication use (eta = 0.187, p = 0.005), Social Welfare Department registration (eta = 0.138, p = 0.036), and the presence of siblings with ASD (eta = 0.130, p = 0.046) were associated with caregiver burden. Multiple linear regression showed that hyperactivity/noncompliance significantly predicted caregiver burden. Conclusion Specific problem behaviours in children with ASD were associated with caregiver burden. These results highlight the need for interventions for the child with ASD and their caregivers.